Nanocomposite Materials for the Sodium–Ion Battery: A Review - Liang, Yaru; Lai, Wei‐Hong; Miao, Zongcheng; Chou, Shu‐Lei (Small (Weinheim an der Bergstrasse, Germany), 2018)
Clean energy has become an important topic in recent decades because of the serious global issues related to the development of energy, such as environmental contamination, and the intermittence of the traditional energy sources. Creating new battery‐related energy storage facilities is an urgent subject for human beings to address and for solutions for the future. Compared with lithium‐based batteries, sodium–ion batteries have become the new focal point in the competition for clean energy solutions and have more potential for commercialization due to the huge natural abundance of sodium. Nevertheless, sodium–ion batteries still exhibit some challenges, like inferior electrochemical performance caused by the bigger ionic size of Na+ ions, the detrimental volume expansion, and the low conductivity of the active materials. To solve these issues, nanocomposites have recently been applied as a new class of electrodes to enhance the electrochemical performance in sodium batteries based on advantages that include the size effect, high stability, and excellent conductivity. In this Review, the recent development of nanocomposite materials applied in sodium–ion batteries is summarized, and the existing challenges and the potential solutions are presented. To explore electrode materials with long cycle life and high energy density, a wide range of nanocomposites have been applied to the anodes and cathodes of sodium batteries. Due to the advantages of nanoscale composites, there have been great improvements in the electrical performance of sodium–ion batteries. The development of nanocomposite materials for sodium–ion batteries is reviewed here.